„Doorgaan en niet vergeten!“ Otto Schumacher (1908–1988). Communist, hulpverlener en verzetsman - Krutzen, Marcel (Historisch Cahier Parkstad Limburg, 2024)
Keywords: Aachen (Region); Antifaschismus; Flüchtlingshilfe; Heerlen; Kommunismus; Konzentrationslager; Politischer Gefangener; Soziale Situation; Steinkohlenbergbau; Widerstand

Spionage in Heerlen tijdens het interbellum. Hoe twee jonge Heerlense meiden het slachtoffer werden van het spel der grootmachten - Dijck, Harry van (MijnStreek, 2020)
Keywords: Heerlen; Spionage

Bevrijding Oostelijke Mijnstreek. Het Amerikaanse leger aan het werk rondom de bevrijding van Hoensbroek en omstreken - Heltzel, Hans (Historische reeks Parkstad Limburg, 2019)
Keywords: Befreiung; Heerlen; Hoensbroek; Südlimburg (Niederlande); Westwall; Zweiter Weltkrieg

Changing Border Regimes. Mining, and Cross-border Labor in the Dutch–Belgian–German Borderlands, 1900–1973 - Knotter, Ad (Journal of Borderlands Studies, 2014)
„In this article the incidence of cross-border commuting to the mining districts in the Belgian–Dutch–German borderlands, known today as the Euregion Meuse-Rhine, will be related to the impact of state borders in different periods. Cross-border labor was closely related to changing border regimes based on uneven economic development, (un)familiarity, and the policy impact of powerful institutions like the state and the church. The main argument is that after the First World War in Dutch Limburg a conscious policy to control the labor force and bind them to mining in the region was relatively successful. Discrepancies in wages and employment opportunities led to border-crossing during restricted periods and for specific groups of workers only.“
Keywords: Grenzarbeitnehmer; Steinkohlenbergbau

The impact of boundaries on cross-border mobility and migration in the Liège-Limburg area (19th–20th centuries) as retrieved from population records - Rutten, Willibrord (Internationales Archivsymposion in Luxemburg (2012). Grenzüberschreitende Migration und Archive. Annalen, mit einem Nachtrag zum Symposion Lüttich (2011) Erster Weltkrieg, 2013)
Keywords: Grenzarbeitnehmer; Steinkohlenbergbau

Alsof de taalgrens niet bestond. Limburgse kompels in de Luikse kolenmijnen na de Tweede Wereldoorlog - Rutten, Willibrord (Het Land van Herle. Historisch tijdschrift voor oostelijk Zuid-Limburg, 2009)
Keywords: Grenzarbeitnehmer; Lüttich; Sprachgrenze; Steinkohlenbergbau; Südlimburg (Niederlande)

Goed betaald? Mijnwerkerslonen en arbeidsmarkt in het Nederlands-Duits-Belgische grensgebied in de achttiende en negentiende eeuw - Gales, Ben A. (Jaarboek Van Het Sociaal Historisch Centrum Voor Limburg, 2008)
Keywords: Grenzarbeitnehmer; Steinkohlenbergbau